Enhancing Sustainability of Cassava Agribusiness in Lampung Province to Ensure Food Security - Endaryanto, Teguh; Firdasari; Seta, Amanda Putra; Saleh, Yuliana (Universitas Muhammadiyah Yogyakarta, 2025)
High demand for cassava in domestic and international markets has raised concerns related to the long-term sustainability of cassava agribusiness. The multifaceted character of sustainability demonstrates the interconnected sustainability across multiple dimensions. This study aims to assess the sustainability index and condition of cassava agribusiness in Lampung Province across various dimensions (economic, sociocultural, technical and technological, institutional, and environmental) and to develop a strategy for cassava agribusiness sustainability to ensure food security. A total of 66 farmer respondents from the two villages were interviewed. Furthermore, FGDs were conducted with traders, local government officials, and factory responders. This research utilized the multi-aspect sustainability analysis (MSA) technique to assess the sustainability status across multiple dimensions. This research concluded that the sustainability status of cassava agribusiness in Lampung Province was less sustainable. This score pertained to economic, technical and technological, and institutional aspects. Meanwhile, social culture and environmental aspects stood in the sustainability category, demonstrating the susceptibility of cassava agribusiness to potential business instability. Cassava agribusiness in Lampung necessitated strategies primarily addressing economic, technical, and technological aspects, along with the establishment of efficient and appropriate institutions to enhance the sustainability of cassava agribusiness in Lampung Province and to ensure food security.